Health education training needs of educators at Makapanstad schools in the North West province - M.D. Peu; L. Napoles; F. Wenhold; K. Mostert-Wentzel; N. Seane (AOSIS, 2010)
Purpose: The purpose of this study was to explore and describe the health education needs of educators at health promoting schools in Makapanstad in North West Province. Methodology: Qualitative, exploratory and descriptive paradigm was conducted. The population consisted of educators, at Makapanstad schools, who were directly involved with learners. The participants were purposively selected. Focus group interviews were conducted to collect relevant data from the participants. Tesch data analysis process was used to reach the findings of the research. Findings: The following categories were identified and theoretically confirmed: The need for the support by the University for the training of educators; The need for the University's acknowledgement of educators' responsibilities; The need for basic knowledge of health promotion; Common health needs of learners; and indirect health problems. Recommendation: It was recommended that a health education package be developed to assist in empowering learners in Makapanstad schools.